The use of gold dinar in international finance : A fund flow approach / Zakarya Ahmad - Ahmad, Zakarya (Research Management Institude, 2005)
This study investigates the relationship between fund Hows and returns in the Malaysian stock market. Both the feedback-trading hypothesis, which states that past returns affect flows, and the information contribution hypothesis, which states that flows affect returns are tested. The result suggests that the direction of causality is from fund Hows to returns and from returns to fund Hows. Therefore, there is a bilateral causality between the two variables. The finding is interesting as it suggests that in the fund Hows determination behavior, the implementation of Gold Dinar will not play a detrimental role as long as the local stock market returns are strong and the overall financial systems are sound for foreign investors